Exploring the interactions between Lactobacillus rhamnosus GG and whey protein isolate for preservation of the viability of bacteria through spray drying. Issue 7 (11th March 2021) - Lu, Wenjie; Fu, Nan; Woo, Meng Wai; Chen, Xiao Dong
Abstract : WPI-treated LGG showed enhanced thermotolerance, with reduced survival and activity after spray drying. WPI treatment might trigger cellular response, causing a decline in metabolic activity and further reducing the stability of cell surface charge. Abstract : Protective agents used in spray drying protect the activity of lactic acid bacteria (LAB) by stabilizing the subcellular structures, constituting a protective layer at the cellular surface, or having mild drying kinetics. The effects of a reputed protectant, whey protein isolate (WPI), on Lactobacillus rhamnosus GG (LGG) were examined by exposing the cells to WPI solution to induce protein adsorption at the cellular surface prior to spray drying. WPI-treated LGG demonstrated enhanced thermotolerance with cell survival increased by 1.64 log after heat treatment. The survival after spray drying was significantly decreased from 45.75% to 8.6% and from 32.96% to 10.44%, when the WPI-treated cells were resuspended in trehalose solution or reconstituted skimmed milk as protectant, respectively, associated with decreased growth capability and metabolic activity. The contact with WPI appeared to stimulate the cellular response of LGG. With well-maintained cell viability and intact cellular membrane, the metabolic activity of WPI-treated LGG was decreased, and subsequent resuspension of the cells in trehalose solution led to a reduction in the stability of the cellular surface charge. The WPI-treated cells showed marginally increased surface roughness, indicating possible WPI attachment, but there was no thick protein coverage at the cellular surface and the size distribution of cells was unaffected. It was proposed that the enhanced thermotolerance and the decreased survival of spray-dried LGG could be linked to the cellular response toward WPI and protectant media, which may vary among individual LAB strains. Modulating the strain-specific interactions between the LAB cells and the protectant constituents could be crucial to maximizing cell viability retention after spray drying.